2016
DOI: 10.1017/s0030605316000661
|View full text |Cite
|
Sign up to set email alerts
|

Are corridors good for tigersPanthera tigrisbut bad for people? An assessment of the Khata corridor in lowland Nepal

Abstract: As part of a landscape-scale programme for conserving tigers Panthera tigris the Khata corridor was established between Bardia National Park in Nepal and Katarniaghat Wildlife Sanctuary in India in early 2000. We examined its functionality by comparing the status of tigers and prey in the corridor and in the adjacent National Park, using camera trapping, transect sampling and diet analysis of scats. Tiger movement was inferred from the photographs, and tiger–human conflict was assessed by means of questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Scat analysis demonstrated that chital was the most important (estimate as biomass) species in the diet for both tigers and leopards as observed in other studies (Lovari et al 2015;Wegge et al 2018). Although there was a large overlap in prey of tigers and leopards, niche separation in the diet was observed with tigers preferring larger-sized prey (Bhattarai and Kindlmann 2012b).…”
Section: Daily Activity Pattern and Dietsupporting
confidence: 68%
See 1 more Smart Citation
“…Scat analysis demonstrated that chital was the most important (estimate as biomass) species in the diet for both tigers and leopards as observed in other studies (Lovari et al 2015;Wegge et al 2018). Although there was a large overlap in prey of tigers and leopards, niche separation in the diet was observed with tigers preferring larger-sized prey (Bhattarai and Kindlmann 2012b).…”
Section: Daily Activity Pattern and Dietsupporting
confidence: 68%
“…About half of the buffer zone is covered by forests/grasslands, the remaining half includes human settlements and agricultural areas (Karki et al 2015). These buffer zone forests have significantly higher human pressure but increasingly are managed for national and foreign ecotourism safaris (Carter et al 2015;Wegge et al 2018). In addition, the communities exploit these forests for fodder, fuelwood, grazing and non-timber forest products following a regulated system of forest use.…”
Section: Study Areamentioning
confidence: 99%
“…Our findings are similar to the findings of Andheria et al (2007), who reported that chital, sambar, gaur, and wild pig constituted 96% of the diet of the tiger from Bandipur Tiger Reserve, India (gaur was not available in our study site). We found that chital was the most common prey species of tigers, as Stoen and Wegge (1996) and Wegge, Yadav, and Lamichhane (2018) reported from Bardia. Our results are different to those of Chitwan National Park where sambar was reported as the main prey species (Kapfer et al, 2011).…”
Section: Discussionsupporting
confidence: 62%
“…When wildlife and humans are sharing the same landscape in close proximity, it is almost impossible to entirely avoid wildlife damage. However, community tolerance of actual and perceived threats can be built through co-management of conflict (Treves et al 2006), including timely compensation for losses, participation in planning and execution of conservation programs, as well as equitable sharing of conservation benefits (Nyhus et al 2005;Wegge et al 2018). Buffer zones are often created surrounding core protected areas to facilitate such processes with dual purpose of maintaining ecological integrity and ensuring participatory conservation or co-management (Budhathoki 2004;Heinen and Mehta 2000;Persoon and Van Est 2003;Sayer 1991;Spiteri and Nepal 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Buffer zones are often created surrounding core protected areas to facilitate such processes with dual purpose of maintaining ecological integrity and ensuring participatory conservation or co-management (Budhathoki 2004;Heinen and Mehta 2000;Persoon and Van Est 2003;Sayer 1991;Spiteri and Nepal 2008). Often in the buffer zone areas, communities are subsidized as compensation for wildlife impacts, while wildlife is protected with refuge habitats and migration corridors (Kolipaka 2018;Sayer 1991;Wegge et al 2018). Reducing negative impacts of wildlife on communities and protecting wildlife and their habitat should be priority actions in the buffer zones (Budhathoki 2004;Heinen and Mehta 2000;Silwal et al 2013).…”
Section: Introductionmentioning
confidence: 99%